2021
DOI: 10.31842/jurnalinobis.v4i4.202
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Melalui Kepuasan Kerja pada Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Kota Tanjungpinang

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh gaya kepemimpinan, budaya organisasi, dan motivasi kerja terhadap kinerja karyawan melalui kepuasan kerja. Responden penelitian ini adalah seluruh pegawai di lingkungan Kantor Badan Pengelolaan Keuangan dan Aset Daerah Kota Tanjungpinang (N = 81). Pengumpulan data dilakukan pada Maret 2021 melalui penyebaran angket yang berisikan 5 skala penelitian yaitu skala gaya kepemimpinan, skala budaya organisasi, skala motivasi kerja, skala kepuasan kerja, dan skala kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(5 reference statements)
4
1
0
3
Order By: Relevance
“…In addition, the Chairperson advises staff members on which tasks should be completed first before starting work activities. This study is consistent with earlier research carried out by (Fahmi, Wibisono, & Satriawan, 2021).…”
Section: Direct Effect Of Leadership On Employee Performancesupporting
confidence: 94%
“…In addition, the Chairperson advises staff members on which tasks should be completed first before starting work activities. This study is consistent with earlier research carried out by (Fahmi, Wibisono, & Satriawan, 2021).…”
Section: Direct Effect Of Leadership On Employee Performancesupporting
confidence: 94%
“…The results of this study are also in line with research conducted by Fahmi, et al (2021), Nyoto & Rajab (2022), and Rustilah (2018, all of which conclude that there is an influence of leadership on performance through job satisfaction.…”
Section: The Influence Of Leadership (X1) On Employee Performance (Y)...supporting
confidence: 91%
“…So, it can be concluded that in order for agencies to improve employee performance, it is not only the factors forming work motivation that need to be considered, but also the factors forming job satisfaction. The results of this study also support several previous studies conducted by Fahmi, et al (2021), Nyoto & Rajab (2022), Flanero, et al (2022), Suristya & Adi (2021) and Haslindah, et al (2022 which all concluded that motivation work on employee performance mediated by job satisfaction has a significant effect.…”
Section: The Effect Of Motivation (X3) On Employee Performance (Y) Th...supporting
confidence: 91%
“…Therefore, it can be inferred that motivation plays a crucial role in enhancing employee performance, and boosting motivation can significantly improve overall performance. These results are in line with Fadhila (2019); Fahmi et al (2021); Feri et al (2020); Pramesti et al (2021); Wijayanto et al (2021); Saharuddin et al (2022), they claims that job motivation has a favorable and considerable impact on performance.…”
Section: The Effect Of Motivation On Performancesupporting
confidence: 81%
“…and Fahmi et al (2021);Fitrianis & Apriliani (2019);Pramesti et al (2021);Wijayanto et al (2021);Saharuddin et al (2022) that motivation has a positive and significant effect on performance Suwandi & Koerniawan (2022)Mubarak & Darmanto (2015);Melisa & Subarto (2021);Ariyadi et al (…”
mentioning
confidence: 99%